Correlation of alterations in the KEAP1/CUL3/NFE2L2 pathway with radiation failure in larynx squamous cell carcinoma. Issue 4 (3rd June 2021) - Sheth, Siddharth; Farquhar, Douglas R.; Schrank, Travis P.; Stepp, Wesley; Mazul, Angela; Hayward, Michele; Lenze, Nicholas; Little, Paul; Jo, Heejoon; Major, M. Ben; Chera, Bhishamjit S.; Zevallos, Jose P.; et al.
Abstract: Objectives: Patients with laryngeal squamous cell carcinoma (LSCC) often fail radiation therapy (RT), when received as monotherapy or in combination with other treatment modalities. Mechanisms for RT failure are poorly understood. We hypothesized that tumors failing RT would have increased rates of somatic mutations in genes associated with radiation resistance, particularly in genes associated with the NFE2L2 oxidative stress pathway. Using targeted exome sequencing on pretreated LSCC tumors, we retrospectively compared somatic mutation profile with clinical data and response to treatment. Methods: Tumors were classified as either radiation‐resistant (RR) or radiation‐sensitive (RS). RR was defined as persistent or recurrent disease within 2 years of receiving full‐dose RT. Early stage (ES) LSCC was defined as Stage I or II tumors without lymph node involvement. Eight genes associated with radiation resistance were prioritized for analysis. RT‐qPCR was performed on five NFE2L2 pathway genes. Results: Twenty LSCC tumors were included and classified as either RR (n = 8) or RS (n = 12). No differences in individual rates of somatic mutations by genes associated with radiation resistance were identified. Higher rates of total mutational burden (TMB) and increased alterations associated with the NFE2L2 pathway was observed in RR vs RS tumors ( P  < .05). In an analysis of only ES‐LSCC patients (RR, n = 3 and RS, n = 3), RR tumors had increased NFE2L2 somatic pathway mutations ( P  = .014) and increased NQO1 mRNA expression ( P  = .05). Conclusion: Increased TMB and NFE2L2 pathway alterations were associated with radiation resistance in LSCC. NQO1 mRNA expression may serve as a biomarker for RT response in ES‐LSCC. Level of Evidence: II1. Abstract : In patients with laryngeal squamous cell carcinoma, we found that mutations in the oxidative stress pathway prior to treatment resulted in increased rates of radiation therapy failures. Higher tumor mutation burden was also associated with radiation resistance.